PENGARUH PENAMBAHAN MATERIAL STOCKPILE KOKONAO SEBAGAI BAHAN BLENDING DENGAN SUPER GRADE ORE TERHADAP KADAR KONSENTRAT DAN RECOVERY LOGAM DALAM PROSES FLOTASI BIJIH TEMBAGA PADA PT. FREEPORT INDONESIA - Utari S. Asmarani; Jance M. Supit (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2019)
PT. Freeport Indonesia is one of the mining company that process the copper and gold ore. One type of ore processed in this company is Super Grade Ore (SGO). The characteristics of SGO are wet and smooth, which can result some problems in transportation. Therefore, it is necessary to do blending process using material from Kokonao stockpile which tends to be drier and rougher, but has the lower grade than Cut of Grade of company. Applying experimental method, this research aims to figure out effects of the addition of Kokonao material in the blending process with SGO on concentrate grade and metal recovery resulted. Overall, the levels of Cu and Au reduce when the Kokonao material added at each various composition, with the lowest Cu grade is 100% Kokonao (1,97%) and the highest Cu grade is 10% Kokonao (25,69%). Meanwhile, the lowest Au grade is 100% Kokonao portion (3,26 ppm) and the highest Au grade is 20% Kokonao (38,16 ppm). In addition, All various compositions result in Cu recovery that is higher than the company standard (>80%). The highest Cu recovery is resulted by 50% Kokonao composition (97,12%).